Design of the Real-Time Single-Photodiode Digital Coherent Receiver Suitable for Free Space Optical Communication - Keji Zhou (IEEE Photonics Journal, 2020)
High sensitivity, small size, light weight and low power are the most critical requirements for the lasercom terminals used in free space optical communication (FSOC) systems. Coherent receivers have an exceptionally high sensitivity but their optical complexity and power consumption are too high, especially for the space-borne lasercom terminals. Recently we propose a pseudo-single-side-band-signal based single-photodiode coherent receiver (P-SCR) with very low optical and algorithm complexity which can potentially satisfy the strict requirement of the FSOC systems. In this paper, we first introduce the working principles of the P-SCR based on the frequency and time domain field reconstruction algorithms (TD-FRA and FD-FRA). We then investigate the relationships between the computation complexity and sensitivity for the two kinds of P-SCR, respectively. We also provide a method to minimize the FD-FRA complexity and demonstrate that its power consumption is only 3.7%, 25.3% and 37.8% of that of the well-known conventional Kramers-Kronig (KK) algorithm, upsampling-free KK algorithm and TD-FRA. Based on the optimized FD-FRA, we develop a highly parallel DSP circuit for the real-time P-SCR using a FPGA chip. The experiments in a 10GBaud QPSK transmission system show that the sensitivity of the real-time P-SCR is only ~4.2 dB away from the theoretical limit.